The femoral anterior tangent line could serve as a reliable alternative reference axis for distal femoral rotational alignment in total knee arthroplasty: an MRI-based study - Li, Shuzhen; Deng, Haiquan; Jiang, Lianjian; Liang, Haibo; Sun, Jianchao; Xu, Youjia (Frontiers in Surgery, 2024)
Background: This study aimed to evaluate the reference value of the femoral anterior tangent (FAT) line as a guidance of distal femoral rotation on magnetic resonance images (MRI). Methods: We retrospectively included 81 patients (106 knees) diagnosed as primary knee osteoarthritis. The indirect rotational axes including the FAT line, the perpendicular line to the anteroposterior axis (pAPA) and the posterior condylar axis (PCA) were identified on MRI, and their angles related to the clinical transepicondylar axis (cTEA) or surgical transepicondylar axis (sTEA) were measured. Patients were further divided into subgroups according to the Kellgren-Lawrence (K-L) grades, the joint-line convergence angle (JLCA) and the arithmetic hip-knee-ankle angle (aHKA) to assess the variance of different rotational reference axes. Results: The FAT line was -11.8° ± 3.6° internally rotated to the cTEA and -7.5° ± 3.6° internally rotated to the sTEA. The FAT/cTEA angle and the FAT/sTEA angle shared a similar frequency distribution pattern but a little greater variance to the pAPA/cTEA angle and the PCA/cTEA angle. The PCA/cTEA angle in JLCA |x| ≥ 6° subgroup was significantly smaller than two other JLCA subgroups. The pAPA/cTEA angle and the PCA/cTEA angle also presented statistical significance within aHKA subgroups. While the FAT/cTEA angle and the FAT/sTEA angle demonstrated superior stable among different K-L grades, JLCA subgroups and aHKA subgroups. Conclusion: The FAT line was less affected by the degree of knee osteoarthritis and lower limb alignment, which could serve as a reliable alternative reference axis for distal femoral rotational alignment in total knee arthroplasty.